Implementasi Strategi Bauran Pemasaran Menurut Ekonomi Islam pada Bisnis Batik Lokal Khas Lebak - Soleh Soleh; Budiman Budiman; Samudi Samudi (Jurnal Hukum Ekonomi Syariah, 2024)
The marketing mix strategy according to Islamic economics must pay attention to the criteria and provisions of good and halal elements that have been determined in Islam, the goal is that the business carried out gets the pleasure of Allah. The current condition, the marketing mix strategy according to Islamic economics has been widely implemented in various businesses or businesses, one of which is in the local batik business typical of Lebak.The purpose of the research is to examine and analyze the implementation of the marketing mix strategy according to Islamic economics in the local batik business typical of Lebak. This research uses a qualitative method with a phenomenological research type, while the data collection technique uses observation and interviews. The results of this study found that the marketing mix strategy according to Islamic economics in the local batik business typical of Lebak has been implemented through aspects of product, price, place and promotion, although not yet optimal. Batik products are made from halal and good materials, have economic value and have many benefits for the community. The sales price of batik is set to regulate distribution and realize a balance between production and consumption levels, and is based on the prevailing market mechanism. The place where batik is sold is good, clean and safe and comfortable, does not interfere with public health or does not cause waste pollution. Batik marketing promotion has been carried out with good attitudes and behavior, cooperative relationships, good service and offering product choices according to consumer desires. The conclusion of this research is that the marketing mix strategy according to Islamic economics has been implemented in the local batik business typical of Lebak. The results of this study are expected to provide new understanding or solutions to the problems faced by local batik entrepreneurs in applying the principles of Islamic economics.